Value Creation and Pricing in Leveraged Buyouts : Empirical evidence from European leveraged buyouts in 1989–2020 - Peltonen, Mikael (My University, 2022)
Private equity returns are considered persistent and have delivered a significant outperformance over public equities. Previous academic literature finds that a major driver in deal returns is EBITDA multiple expansion i.e. the difference between entry and exit pricing. EBITDA multiple expansion is an output of successful negotiations and ability to acquire portfolio companies with lower entry multiples and sell them with higher exit multiples. While EBITDA multiple expansion is found to be a fundamental factor explaining equity returns, the underlying determinants are less studied subject. To further shed a light of underlying mechanisms behind EBITDA multiple expansion, this thesis focuses on the determinants of entry and exit pricing (multiples). Different determinants and their influence on entry and exit pricing is tested in two phases with different regression models. Determinants are divided into three different categories: company-specific (deal) characteristics, fund characteristics, as well as sector characteristics. Data set is provided by the Finnish fund of funds and consists of over 1,000 transactions from the several European private equity fund managers compiled as a part of their due diligence efforts. Furthermore, empirical analysis is conducted on a transaction level by using this cross-sectional sample of unique LBO transactions. Determinants and their influence on entry and exit pricing is tested with a linear regression model (OLS). Results are mainly in line with the previous studies and testable hypothesis. Entry pricing is positively influenced by the precedent transactions in M&A market, portfolio company’s operating performance and deal size. Surprisingly, PE fund reputation and experience do not result more favourable entry pricing. Exit pricing is also positively explained by the precedent transactions in M&A market, portfolio company’s operating and PE fund experience and reputation. Results indicate that different exit types have a major influence on exit multiples.
Keywords: Private Equity, Entry and Exit Pricing, Value Creation, Leveraged Buyouts, Multiple Expansion